Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Literasi Kisah Nabi Ibrahim Melalui Aplikasi Powerpoint Siswa Kelas IV SDN 005 Bontang Selatan Tahun Pelajaran 2024/2025 - Fadliansyah, Muhammad Ibnu (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to describe the efforts of Islamic Religious Education (PAI) teachers in improving literacy in the story of the Prophet Ibrahim through the PowerPoint application for grade IV students of SDN 005 Bontang Selatan in the 2024/2025 Academic Year. This study uses a descriptive qualitative approach with data collection techniques in the forms of observation, interviews, and documentation. The main focus of this study is to determine the efforts of teachers in designing and using PowerPoint as a learning medium that supports students' understanding of the content and values in the story of the Prophet Ibrahim. Data analysis techniques in this study were carried out through data reduction, data presentation, and drawing conclusions. The results showed that PAI teachers played an active role in designing PowerPoint materials with visual elements, simple text, and audio to attract students' attention. Teachers also integrated PowerPoint with discussion methods, questions and answers, and value-based evaluations, which encouraged students' active involvement in learning. PowerPoint has proven effective in helping students understand the storyline, identifying exemplary values, and fostering interest in the stories of the prophets. This media also makes it easier for teachers to explain the material systematically and in accordance with the students' learning styles.Although there are obstacles such as limited time and equipment, teachers are able to overcome them with careful planning and creativity in delivering the material. Thus, the use of the PowerPoint application is a strategic alternative in Islamic Religious Education learning that is able to improve students' religious literacy from an early age.